Implementation of Quantum Teaching Models to Improve The Skill of Reading The Poetry Of VIII Grade Students of SMP 1 Mesuji OKI - Hermiati; Wardiah, Dessy; Fitriani, Yessi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This classroom action research entitled Application of the Quantum Teaching Model to Improve Class VIII Poetry Reading Skills of SMP Negeri 1 Mesuji OKI involved 27 grade VIII students. This research was conducted for two cycles with a span of three weeks per cycle. Based on the results of the analysis of teacher observation data, it is known that the level of teacher competence in teaching is very good, namely, 3.88 in the first cycle and 4 in the second cycle. The percentage of students' observation scores also experienced a very significant increase, if in the first cycle it only touched 51.85%, but in the second cycle, it became 77.77%. The results of students' poetry reading scores also increased very well. In the first cycle, the percentage of success only reached 46.42% but increased to 100% in the second cycle